PERBAIKAN KINERJA PRODUKSI ENTING-ENTING GETI DENGAN PENYANGRAI DAN PENGGILING KACANG - Rini Yulianingsih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2016)
ABSTRACTEnting-enting Geti is one of the superior products that produced by micro and small-scale agro-industries (SMEs) in Karangsari District Blitar City. Service activities aimed to improve the SMEs (Enggal Jaya and Cemara Jaya) productivity in Enting-enting Geti production through technological improvement, and the enhancement of management and production system. Application of new peanut roasters and grinder had improved production efficiency. Roasting capacity increased to 50 kg/h of 6-7 kg / h, while the milling capacity increased to 5 kg / h of 2 kg / h. The product quality Improvements are the homogeneity of size, color and texture of the peanut, as well as the improvement of hygiene and product safety since the previous tools using corrosive materials. The advantages of using the new equipment are the energy cost savings and faster processing that had impacted on the production costs reduction, and provides the better for quality and perfomance.